2012
DOI: 10.5551/jat.11569
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of Atherosclerosis and Hepatic Oxidative Stress are Independent of Exercise Intensity in LDLr<sup>-/-</sup> Mice

Abstract: ) and G3 (0.014±0.001 cm 2 ) presented lower aortic fat deposition than G1 (0.039±0.005 cm 2 ). G2 and G3 exhibited higher HDL-C, TG and CAT activity, but lower lipid peroxidation and carbonyl protein than G1. SOD values were higher in G3 than G2 and G1, and GPx was higher in G2 than in G3 and G1. Conclusions: Our protocols of low-and moderate-intensity aerobic exercise training (30 min daily for 8 weeks) induced similar benefits in LDLr −/− mice with atherosclerosis.J Atheroscler Thromb, 2012; 19:904-911.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
1
10
0
2
Order By: Relevance
“…Alternatively, exercise training failed to increase HDL-C concentrations in our C57BL/6 mouse model, an effect, that is, most often associated with aerobic exercise training in humans [41] but has been shown to be quite variable in rodents [40, 4244]. This nonresponse of HDL-C is likely model specific as C57BL/6 mice carry the majority (~70%) of plasma cholesterol in the HDL fraction and exhibit modified HDL metabolism characterized by an absence of cholesterol-ester transfer protein and a resistance to diet-induced atherosclerosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, exercise training failed to increase HDL-C concentrations in our C57BL/6 mouse model, an effect, that is, most often associated with aerobic exercise training in humans [41] but has been shown to be quite variable in rodents [40, 4244]. This nonresponse of HDL-C is likely model specific as C57BL/6 mice carry the majority (~70%) of plasma cholesterol in the HDL fraction and exhibit modified HDL metabolism characterized by an absence of cholesterol-ester transfer protein and a resistance to diet-induced atherosclerosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concentrations of glutathione in the hepatic tissues were significantly high in the MCP-3 mice compared with the wild-type mice. Hepatic antioxidant enzymes have been recognized to be closely associated with liver damage and atherosclerosis caused by oxygen radicals [9,17,30]. According to the results in this study, the MCP-3 mice seemed to be more sensitive to the atherogenic diet and more vulnerable to oxidative stress and further progression of atherosclerosis.…”
Section: Hepatic Antioxidant Enzyme Activitiesmentioning
confidence: 55%
“…Clinical studies have shown that formation of ROS is a critical event in the development of atherosclerosis [110] and upregulation of oxidative stress and downregulation of the antioxidant defense mechanism are evident in subjects with coronary artery disease (CAD) [137]. Therefore, regulation of redox status and metabolism of lipoproteins have been proposed as two potential mechanisms through which exercise promotes beneficial effects on atherosclerosis [139].…”
Section: Effect Of Exercise On Atherosclerosis and Oxidative Stressmentioning
confidence: 99%
“…Previous studies proposed that increased activation antioxidant enzymes may reduce atherosclerosis through the co-activation of vascular relaxation mediated by NO, as the superoxide (O 2 − ) dismutation increases the bioavailability of NO in endothelial cells and in the presence of the O 2 − NO shifts to formation of peroxynitrite (ONOO − ) [137,152,153]. Furthermore, according to Teodoro et al [139], moderate-and low-intensity CVE training performed daily for 30 min over an 8-week period, increased the activity of the antioxidant enzymes SOD and GPx, decreased lipid hydroperoxides and PC formation and decreased atherosclerotic lesions in mouse models with atherosclerosis.…”
Section: Effect Of Exercise On Atherosclerosis and Oxidative Stressmentioning
confidence: 99%